On the unique features of post‐disaster humanitarian logistics - Holguín‐Veras, José; Jaller, Miguel; Van Wassenhove, Luk N.; Pérez, Noel; Wachtendorf, Tricia (Journal of Operations Management, 2012)
AbstractLogistic activity can be thought of as a socio‐technical process whereby a social network of individuals orchestrates a series of technical activities using supporting systems such as transportation and communications. To understand the functioning of the entire system requires proper consideration of all its components. We identify seven key components: the objectives being pursued, the origin of the commodity flows to be transported, knowledge of demand, the decision‐making structure, periodicity and volume of logistic activities, and the state of the social networks and supporting systems. Based on our analysis of the differences between commercial and humanitarian logistics, we pinpoint research gaps that need to be filled to enhance both the efficiency of humanitarian logistics and the realism of the mathematical models designed to support it.We argue that humanitarian logistics is too broad a field to fit neatly into a single definition of operational conditions. At one end of the spectrum we find humanitarian logistic efforts of the kind conducted in long‐term disaster recovery and humanitarian assistance, where operational efficiency – akin to commercial logistics – is a prime consideration. At the other, post‐disaster humanitarian logistic operations involved in disaster response and short‐term recovery activities represent a vastly different operational environment, often in chaotic settings where urgent needs, life‐or‐death decisions and scarce resources are the norm. The huge contrast between these operational environments requires that they be treated separately.